2019
DOI: 10.1111/and.13397
|View full text |Cite
|
Sign up to set email alerts
|

Classifying seminal vesicle cysts in the diagnosis and treatment of Zinner syndrome: A report of six cases and review of available literature

Abstract: This study aims to emphasise the importance of imaging in the diagnosis and treatment decision‐making in Zinner syndrome and provide a classification for seminal vesicle cysts. The data of six patients with Zinner syndrome in a single institution were collected. All patients underwent a contrast‐enhanced computed tomography (CT) exam. Among these patients, five patients also underwent an magnetic resonance imaging (MRI). These results were combined with the review of available literature to classify the semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“… [2] Small sized testis and ureterocele of the same side have also been reported. [7] On digital rectal examination there may be presence of well-defined cystic lesion palpable adjacent to the seminal vesicle however it can remain undetected on physical examination. [8] …”
Section: Discussionmentioning
confidence: 99%
“… [2] Small sized testis and ureterocele of the same side have also been reported. [7] On digital rectal examination there may be presence of well-defined cystic lesion palpable adjacent to the seminal vesicle however it can remain undetected on physical examination. [8] …”
Section: Discussionmentioning
confidence: 99%
“…Recently, robotic-assisted interventions have shown to have curative potential in patients with long-standing local symptoms [10]. For patients with only symptoms related to seminal vesicle cysts, literature favors the transurethral unroofing as the treatment option [11]. Van den Ouden et al, while reporting data for 52 patients, demonstrated a 100% success rate of surgical excision of seminal vesicle cysts compared to a 75% success rate with transurethral unroofing [12].…”
Section: Discussionmentioning
confidence: 99%
“…La asociación de esta entidad nace del origen embriológico común del riñón y la vesícula seminal, a partir del conducto mesonéfrico o de Wolff, y es secundaria a una alteración en la embriogénesis entre las semanas 4 y 13 de gestación. (5,6) Normalmente, la yema ureteral asciende desde la parte dorsal del conducto mesonéfrico distal y se extiende dorsocranealmente para encontrarse con el blastema metanéfrico e inducir su diferenciación, formándose así el riñón. El conducto mesonéfrico se diferenciará en el epidídimo, conducto deferente, vesícula seminal, conducto eyaculador y hemitrígono.…”
Section: Discussionunclassified